{Fate of the C-1 ' peroxyl radical in the 2 '-deoxyuridine system} - Chatgilialoglu, C; Gimisis, T. (Chem. Commun., 1998)
The mechanism of 2-deoxyribonolactone formation from the reaction of photogenerated 2'-deoxyuridin-1'-yl radical with molecular oxygen in water has been investigated.